Análise da volatilidade de preço do mercado da borracha natural - Caproni, Tiago Vieira (2008)
The core of this research was to develop an analysis of price trajectory from rubber through the XX century, using econometrics test from the ARCH class: GARCH, EGARCH and TARCH to calculate the international price volatility of physical rubber, based on the price of Malaysian Rubber Exchange main entity in the sector. As results from the statistical tests available in the market, it was possible to observe a strong incidence of seasonal cycles in the international price of rubber that impacts directly in the world production. It is also possible to notice the low capacity of production to answer shocks of demand due to long time to mature the plantation.